2007
DOI: 10.4049/jimmunol.178.12.7710
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Telomerase Activity in Highly Differentiated CD8+CD28−CD27− T Cells Is Associated with Decreased Akt (Ser473) Phosphorylation

Abstract: The enzyme telomerase is essential for maintaining the replicative capacity of memory T cells. Although CD28 costimulatory signals can up-regulate telomerase activity, human CD8+ T cells lose CD28 expression after repeated activation. Nevertheless, telomerase is still inducible in CD8+CD28− T cells. To identify alternative costimulatory pathways that may be involved, we introduced chimeric receptors containing the signaling domains of CD28, CD27, CD137, CD134, and ICOS in series with the CD3 zeta (ζ) chain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(227 citation statements)
references
References 55 publications
6
216
1
Order By: Relevance
“…A recent study has suggested that CD8+ CD28¡ T cells are able to upregulate telomerase activity but that CD8+ CD28¡ CD27¡ T cells cannot [118]. Both telomerase activity and proliferation by CD8+ CD28¡ CD27¡ T cells following anti-CD3 and APC stimulation were restored almost to the level of other CD8+ T cells on the addition of IL-2 or IL-15 [118].…”
Section: What Is the Capacity Of Cd8+ Cd45ra+ Cd28¡ T Cells To Prolifmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent study has suggested that CD8+ CD28¡ T cells are able to upregulate telomerase activity but that CD8+ CD28¡ CD27¡ T cells cannot [118]. Both telomerase activity and proliferation by CD8+ CD28¡ CD27¡ T cells following anti-CD3 and APC stimulation were restored almost to the level of other CD8+ T cells on the addition of IL-2 or IL-15 [118].…”
Section: What Is the Capacity Of Cd8+ Cd45ra+ Cd28¡ T Cells To Prolifmentioning
confidence: 77%
“…An early study showed that CD45RA+ cells had longer telomeres than CD45RO+ cells [115], however, separating CD45RA+ T cells, which lack CD27 expression (memory cells) showed that their telomere length was similar to CD45RO+ memory cells [116,117]. A recent study has suggested that CD8+ CD28¡ T cells are able to upregulate telomerase activity but that CD8+ CD28¡ CD27¡ T cells cannot [118]. Both telomerase activity and proliferation by CD8+ CD28¡ CD27¡ T cells following anti-CD3 and APC stimulation were restored almost to the level of other CD8+ T cells on the addition of IL-2 or IL-15 [118].…”
Section: What Is the Capacity Of Cd8+ Cd45ra+ Cd28¡ T Cells To Prolifmentioning
confidence: 99%
“…8 , 9 The loss of both CD28 and CD27 molecules defines a late differentiation status of T cells. 10 , 11 On the other hand, inhibitory receptors, including Lymphocyte-activation gene 3 (LAG-3), T-cell immunoglobulin and mucin domain-3 (TIM-3) and Programmed death-1 (PD-1) have been strongly associated with “T-cell exhaustion”. 12 , 13 However, PD-1 expression may also reflect a particular differentiation and/or activation status of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies showed that frequencies of highly cytotoxic CD8 + CD28 − T cells in inflamed muscle and in peripheral blood of IBM patients are significantly increased and their capability to secrete IFN γ was superior compared to healthy controls 82, 83. CD8 + CD28 − T cells are devoid of costimulatory interaction between CD80:CD28, however, it is reported that CD8 + CD28 − T cells after CD3 ligation in turn upregulate alternative costimulatory molecules such as inducible costimulator (ICOS), CD134 and CD13784 which could facilitate T cell: muscle fiber interaction and is in keeping with the observed upregulation of ICOS‐L on muscle fibers during IBM 48…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%
“…It is believed that CD8 + CD57 + T cells are highly differentiated antigen‐driven effector cells in a state of replicative senescence with limited capacities to proliferate 88, 89, 90, 91, 92. Recent reports, however, suggest that these CD8 + CD57 + CD28 − T cells might comprise a rather heterogeneous group of highly antigen‐experienced cells that, depending on the immunobiological context and stimuli, differ in their susceptibility to apoptosis and their capability to proliferate and expand 84, 93, 94, 95…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%